2014
DOI: 10.5194/acp-14-1557-2014
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic and chemical characterisation of Po Valley aerosol

Abstract: www.atmos-chem-phys.net/14/1557/2014/ doi:10.5194/acp-14-1557-201

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
2
8
1
Order By: Relevance
“…These figures are in keeping with the growth factors reported for the Po Valley by Svenningsson et al (1992) and by Bialek et al (2013), who measured HGfs of 1.44 ± 0.14 and 1.46, respectively.…”
Section: Drh Comparisonsupporting
confidence: 76%
“…These figures are in keeping with the growth factors reported for the Po Valley by Svenningsson et al (1992) and by Bialek et al (2013), who measured HGfs of 1.44 ± 0.14 and 1.46, respectively.…”
Section: Drh Comparisonsupporting
confidence: 76%
“…S2, the average GF of 110 nm and 165 nm particles showed a clear diurnal pattern, which peaked at about 11:00 every day and reached a minimum at 20:00. This trend was similar to the GF observation in Po Valley (Bialek et al, 2014) or Oklahoma site (Mahish and Collins, 2017) and is often attributed to a shallower and more stagnant boundary layer during the night with temperature inversions arising from radiative cooling of the surface.…”
Section: Continental Air Massessupporting
confidence: 83%
“…This is different from those found in other studies in urban air. Lance et al (2013) and Bialek et al (2014) observed larger mean  value than in the present work, and its diurnal variability was different.…”
Section: Diurnal Variabilitycontrasting
confidence: 53%